2017
DOI: 10.1016/j.jpeds.2017.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Kidney Injury in Children Receiving Nonsteroidal Anti-Inflammatory Drugs After Cardiac Surgery

Abstract: Objective To investigate the association of nonsteroidal anti-inflammatory drug (NSAID) administration with urinary neutrophil gelatinase-associated lipocalin (NGAL) levels in children following cardiopulmonary bypass (CPB) who did not develop acute kidney injury (AKI). Study design In this prospective observational study, urinary NGAL levels were investigated in 210 children who underwent cardiothoracic surgery requiring CPB. Children with clinical AKI (increase in serum creatinine ≥50% from baseline within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…We then further classified AKI by integrating the functional biomarkers creatinine and cystatin C with the damage biomarker NGAL, in accordance with the paradigm set forth by the Tenth Consensus Conference of the Acute Dialysis Quality Initiative and applied in other populations (Fig. 2) [21,22,[31][32][33]. We used the definitions of Composite AKI Types shown in Fig.…”
Section: Aki Definitionsmentioning
confidence: 99%
“…We then further classified AKI by integrating the functional biomarkers creatinine and cystatin C with the damage biomarker NGAL, in accordance with the paradigm set forth by the Tenth Consensus Conference of the Acute Dialysis Quality Initiative and applied in other populations (Fig. 2) [21,22,[31][32][33]. We used the definitions of Composite AKI Types shown in Fig.…”
Section: Aki Definitionsmentioning
confidence: 99%
“…In a retrospective study of cardiac surgical patients using the NINJA collaboration definition (17), Uber et al found that 85% of cardiac ICU patients received at least 1 nephrotoxin and 21% received ≥3 nephrotoxins, demonstrating suboptimal adherence this recommendation as well (18). The most common nephrotoxin that was administered was non-steroidal anti-inflammatory agents (ketorolac and/or ibuprofen), which are used widely in post-operative pediatric cardiac patients and have been associated with subclinical kidney injury even in patients without AKI (19).…”
Section: Therapeutic Targetsmentioning
confidence: 99%
“…Several kidney tubule biomarkers are used by the U.S. Food and Drug Administration for drug safety evaluation in early phase studies, and many of these markers have been leveraged to characterize nephrotoxicity associated with tenofovir and antihypertensive therapy 29,30,44,45 . Studies of children and adults undergoing NSAID therapy showed that even with brief high‐intensity NSAID use, tubule injury biomarkers rise before and independently of serum creatinine 31,46 . However, we observed no evidence of kidney tubule injury or dysfunction among NSAID users in the Health ABC cohort despite the use of an array of biomarkers capturing multiple dimensions of kidney health in a large sample of at‐risk individuals.…”
Section: Discussionmentioning
confidence: 56%
“…Measures include biomarkers of tubule injury (kidney injury molecule‐1 (KIM‐1), interleukin‐18 (IL‐18), and neutrophil gelatinase‐associated lipocalin (NGAL)); tubulointerstitial fibrosis (propeptide type III procollagen (PIIINP)); proximal tubule resorptive function (alpha‐1 microglobulin (α1m)); and tubule synthetic function (uromodulin (UMOD)). These investigational biomarkers are sensitive indicators of early kidney tubule damage in the setting of medication toxicity, including NSAID nephrotoxicity, and are also associated with long‐term outcomes 22‐31 . Importantly, they have been applied across the age spectrum and are associated with cardiovascular disease, heart failure, and mortality in older adults 32‐34 …”
Section: Introductionmentioning
confidence: 99%